Networking All-in-One Desk Reference for Dummies 2nd Edition - Lowe, Doug (Wiley Publishing, 2011)
If you're setting up a network at home or creating and managing one for business, there are dozens of things to consider. Networking All-In-One Desk Reference For Dummies, 2 nd Edition replaces a whole shelf full of reference books with one handy volume that covers just what you need to know. And with technology changing faster than the colors in a rock band's light show, you'll be glad this updated edition includes the latest information. Written by Doug Lowe, who's been managing corporate networks for more than 20 years, this helpful guide shows you how to work with all Windows XP service packs as well as Fedora Linux. It's made up of nine minibooks that cover Networking basics Building a network Network administration and security Troubleshooting and disaster planning TCP/IP and the Internet Home networking Wireless networking Windows 2003 server reference Linux reference If you're a networking newbie, the first two minibooks gives you all the startup information to get your network up and running. If you've already done that, you're probably interested in keeping it running at peak performance. Book IV is loaded with information about finding, diagnosing, and fixing problems you might encounter. Looking for the scoop on keeping your network safe from online bad guys? Check Book III. Want to go wireless? Book VII tells you what you need to know. In these pages, you'll find out how to Plan your network, select interface cards, hubs, and routers, and install all the hardware and software Set up your network so it's easy to use but hard to break into Create a disaster recovery plan Understand IP addresses, subnetting, routing, DHCP, DNS, and other TCP/IP protocols and tools Incorporate other gadgets into your home network, including VoIP Internet-based telephone service Take advantage of the economical Linux networking alternative Best of all, it's easy to locate what you need. There's even a handy "cheat sheet" that puts really important information about cabling rules, private IP address ranges, valuable network administration tips, and helpful Web sites at your fingertips. With this book on hand, you'll experience a net increase in your networking prowess!